2012
DOI: 10.3390/md10122698
|View full text |Cite
|
Sign up to set email alerts
|

Lipids of Prokaryotic Origin at the Base of Marine Food Webs

Abstract: In particular niches of the marine environment, such as abyssal trenches, icy waters and hot vents, the base of the food web is composed of bacteria and archaea that have developed strategies to survive and thrive under the most extreme conditions. Some of these organisms are considered “extremophiles” and modulate the fatty acid composition of their phospholipids to maintain the adequate fluidity of the cellular membrane under cold/hot temperatures, elevated pressure, high/low salinity and pH. Bacterial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…5 Variation of the content of PUFA in relation to the zeta potential of the R. erythropolis cells exposed to 1-7.5 % (w/w) NaCl these conditions were about 1 order of magnitude lower than those observed in the present study. Fulco demonstrated that bacilli and mycobacteria could produce dienoic fatty acids by aerobic desaturation of fatty acids (Fulco 1974), but recent studies link the fatty acid composition to the bacterial ecological niche (de Carvalho and Caramujo 2012;de Carvalho and Fernandes 2010;Nichols 2003). As previously mentioned, it is generally accepted that only few bacteria are capable of synthesising PUFAs, whereby most of them are marine bacteria, in particular from cold, deep-sea sediments, fish and water (Hamamoto et al 1995;Yano et al 1998;Yano et al 1997).…”
Section: Fast Adaptations To the Presence Of Sodium Chloridementioning
confidence: 91%
See 1 more Smart Citation
“…5 Variation of the content of PUFA in relation to the zeta potential of the R. erythropolis cells exposed to 1-7.5 % (w/w) NaCl these conditions were about 1 order of magnitude lower than those observed in the present study. Fulco demonstrated that bacilli and mycobacteria could produce dienoic fatty acids by aerobic desaturation of fatty acids (Fulco 1974), but recent studies link the fatty acid composition to the bacterial ecological niche (de Carvalho and Caramujo 2012;de Carvalho and Fernandes 2010;Nichols 2003). As previously mentioned, it is generally accepted that only few bacteria are capable of synthesising PUFAs, whereby most of them are marine bacteria, in particular from cold, deep-sea sediments, fish and water (Hamamoto et al 1995;Yano et al 1998;Yano et al 1997).…”
Section: Fast Adaptations To the Presence Of Sodium Chloridementioning
confidence: 91%
“…This assumption was derived probably, as pointed out by Okuyama et al (2007), from the fact that the best studied bacterial species in terms of physiology, biochemistry and molecular biology were mesophilic species such as Escherichia coli containing no PUFAs. It is now accepted that long-chain PUFAs, such as EPA, DHA and ARA, are preferentially produced by marine bacteria (de Carvalho and Caramujo 2012;DeLong and Yayanos 1986;Hamamoto et al 1995;Nichols 2003;Russell and Nichols 1999). PUFAs may also easily be decomposed by autoxidation during analytical procedures or by harsh transesterification methods, e.g.…”
Section: Fast Adaptations To the Presence Of Sodium Chloridementioning
confidence: 99%
“…However, few bacteria, such as methanotrophic bacteria, are known to produce sterols (Schouten et al 2000;Volkman 2003) and it is accepted that some species do have the capacity to produce eicosapentaenoic acid (20:5x3, EPA), docosahexaenoic acid (22:6x3, DHA) or arachidonic acid (20:4x6, ARA) (Watanabe et al 1997;de Carvalho & Caramujo 2012). The phylogeny and distribution of marine bacteria that do produce n-3 PUFAs has been reviewed by Russell and Nichols (1999) and by Nichols and McMeekin (2002).…”
Section: Nutritional Constituents In Bacteriamentioning
confidence: 99%
“…Bacteria play important roles in marine environments, including driving biogeochemical cycles (Paerl and Pinckney, 1996;Hawley et al, 2017) and supplying materials and energy to higher trophic levels (Azam et al, 1983;de Carvalho and Caramujo, 2012). The phenotypic plasticity of bacteria is responsible for their success and ubiquity (Brown and Williams, 1985;López-Maury et al, 2008).…”
Section: Introductionmentioning
confidence: 99%